Juridical Review Of The Implementation Of Corporate Social Responsibility (Csr) In The Perspective Of Community Empowerment - Subhi Subarka; Fahmy Fauzan Alawy; Muhammad Ivan AlRasyid; Harmono Harmono; Agus Dimyati (PT Publikasiku Academic Solution, 2024)
This research discusses environmental social responsibility or Corporate Social Responsibility (CSR), which has become a global issue and has received wide attention from various stakeholders. Many companies in Indonesia, including PT Japfa Comfeed, need to be fully aware of the importance of social and environmental responsibility. This research aims to understand the implementation of CSR programs at PT Japfa Comfeed and its relation to improving the social welfare of the surrounding community. The method used is an empirical juridical approach, which is an approach based on applicable Law and the reality of practice in the field. The study results show that the implementation of CSR at PT Japfa Comfeed benefits the social conditions of the surrounding community, even though the implementation could be more optimal. This is due to unclear legal regulations, so practical guidelines are needed to avoid causing various interpretations. In conclusion, CSR at PT Japfa Comfeed must be carried out continuously to ensure maximum benefits for all parties, especially those needing attention and support.